PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE PRACTICE-REHEARSAL PAIRS TERHADAP PEMAHAMANKONSEP MATEMATIS SISWA KELAS X SMA PGRI 1 PADANG TAHUN PELAJARAN 2013/2014 - Juliana, Mira; Febriana, Rina; Yuliana Fitri, Dewi (STKIP PGRI Sumbar, 2014)
ABSTRACTThe research was conducted based on the fact which indicated the (1) low students ability to interact each others, (2) low students comprehension about mathematical concept and (3) low students achievement in mathematical subject. The purpose of this research was to know whether the students treated by Practice-Rehearsal Pairs strategy have better comprehension of mathematical concept than those who are treated by conventional strategy in SMA PGRI 1 Padang. This was an experimental research which used random sampling. The population was the X grade students in which X1 was the experimental class while the X4 class was the control class. The hypotheses was tested by using t-test. It was found that t-obtained (4.67)> t-table (1.67). Thus, the hypothesis is accepted. It can be concluded that the students treated by Practice-Rehearsal Pairs strategy had better mathematical comprehension than those who treated the conventional strategy.